A Pooled Analysis of the Cardiac Events in the Trastuzumab Adjuvant Trials - de Azambuja, Evandro (Breast Cancer Res Treat, 2019)
BACKGROUND: Trastuzumab-associated cardiotoxicity remains an issue for patients with HER2-positive breast cancer. This pooled analysis of 3 adjuvant trials investigated the incidence, timing, impact on treatment completion and risk factors for trastuzumab-associated cardiotoxicity. METHODS: This is an individual patient data level pooled analysis of HERA, NSBAP B-31, and NCCTG 9831 (Alliance Trials). Definitions of cardiac events were as per each individual study. RESULTS: A total of 7,445 patients enrolled in the 3 trials were included in the analysis, of which 4,017 were in the trastuzumab and 3,428 in the control (observation) arms, respectively. Median follow-up exceeded 10 years (119.2 – 137.2 months). Nearly all patients (97.4%) in the trastuzumab arms received anthracycline-based chemotherapy. In total, 452 patients in the trastuzumab arms experienced a cardiac event (11.3%), with most being mildly symptomatic or asymptomatic left ventricular ejection fraction (LVEF) decrease (351 patients, 8.7%). Severe congestive heart failure was more common in the trastuzumab arm (2.3%) than in the control arm (0.8%). Most cardiac events occurred during trastuzumab treatment (78.1%) and cardiac events were the main cause of discontinuation across the sample (10.0%); nevertheless, a large majority of patients completed trastuzumab treatment (76.2%). Baseline risk factors that were significantly associated with development of cardiac events were baseline LVEF <60%, hypertension, body mass index >25, age ≥60 and non-Caucasian ethnicity. CONCLUSION: One year of trastuzumab increases the risk of cardiac events, though most consist of asymptomatic or mildly symptomatic LVEF drops. Adjuvant trastuzumab should be considered a safe treatment from a cardiac standpoint for most patients. Trastuzumab-associated cardiotoxicity is the main cause of discontinuation and further research is needed to individualize prevention and management.